Using Electromagnetic Navigation Bronchoscopy and Dye Injection to Aid in Video-Assisted Lung Resection. Issue 11 (November 2016) - Brown, Jordan; Lee, Thomas J.; Joiner, Theresa; Wrightson, William
Small (2 cm) peripheral lung lesions and ground glass opacities remain a difficult subset of lung lesions for the diagnosis and management of lung cancer. Surgical biopsy is more difficult for these lesions because intraoperative localization has to be made without the aid of direct visualization or manual palpation. Electromagnetic navigation bronchoscopy can be used in the operating room to identify a small peripheral lesion and marked using an injection of methylene blue, which can be seen on the visceral pleura of the lung. We present our initial experience using this technique. The sample was eight patients who had peripheral lesions with an average size of 19 mm. Surgical wedge biopsy was diagnostic in all cases, with an average procedure time of 28 minutes. There were no complications from this procedure. In conclusion, these data suggest that electromagnetic navigation bronchoscopy can be performed safely with high diagnostic accuracy by the operating thoracic surgeon, but further data are needed to establish its utility and safety.